Design and Performance Analysis of Cold Rolled Steel Structures in A Two-Story House Based on SNI 7971:2013 - Andun Sulistyo Darmawan; Data Iranata (Green Publisher Indonesia, 2025)
This research aims to design cold-rolled steel (CFS) structures in two-story residential buildings by referring to the SNI 7971:2013 standard. The methodology used includes structural modeling using SAP 2000 software to analyze the strength and stability of the building. The data used includes technical parameters of cold rolled steel as well as relevant dead load, live load, wind load and earthquake load criteria. The results of this research show that the application of cold rolled steel to a two-story building structure produces strength and stability that meets standards. Analysis indicates that cold-rolled steel has significant advantages such as high strength, light weight, and design flexibility, so it can be applied to various structural components, including roof frames, walls, and floors. In addition, cold rolled steel has proven to be efficient in the construction process and is resistant to corrosion and fire, making it an economical and durable material. This research provides detailed guidance in modeling and analyzing building structures using SAP 2000, which is very useful for engineers and construction practitioners. It is hoped that the findings of this research will support better decision making regarding the optimal use of materials and construction methods for two-story buildings, as well as encourage further innovation in the application of cold-rolled steel in multi-storey building construction.